2013
DOI: 10.1080/21650349.2013.799309
|View full text |Cite
|
Sign up to set email alerts
|

Inspiration peak: exploring the semantic distance between design problem and textual inspirational stimuli

Abstract: The selection of sources of inspiration is a crucial moment while designing, as it can enhance design creativity. Designers seem to prefer using pictorial representation modalities despite empirical investigations indicating possible disadvantages of such unimodal approaches. Therefore, it is valid to ask whether designers are disregarding other available stimuli, such as textual representations. In order to answer this question and to find out about the usefulness of different textual stimuli during ideation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 31 publications
2
41
1
Order By: Relevance
“…The effect of trends and patents on the novelty of design proposals is not positive compared to control group, while the majority of previous researches show that examples and previous solutions increase novelty; e.g. Gonçalves et al (2013), Goldschmidt (2011). Trends and patents are not effective in increasing novelty in the scope of this research, but this can also depend on the higher acceptable degree of novelty this research aims at capturing, with reference to NGTS.…”
Section: Discussioncontrasting
confidence: 55%
“…The effect of trends and patents on the novelty of design proposals is not positive compared to control group, while the majority of previous researches show that examples and previous solutions increase novelty; e.g. Gonçalves et al (2013), Goldschmidt (2011). Trends and patents are not effective in increasing novelty in the scope of this research, but this can also depend on the higher acceptable degree of novelty this research aims at capturing, with reference to NGTS.…”
Section: Discussioncontrasting
confidence: 55%
“…In many cases, humans exert their judgment to select appropriate levels of abstraction, and also do extensive screening of possible matches based on whether they overlap with key properties/constraints in the original problem context. This is important because analogies that are "too far" away can actually lead to less creative ideas [5,9,13]. Yu et al [29] recently showed that describing the problem context in abstract terms, but retaining a domainspecific description of its key constraints, enabled crowd workers to find more useful far inspirations than a representation that is abstract on both the problem context and its constraints: for example, the description "make an object (abstracted problem context) that does not tip over easily (concrete constraint)" yields more useful inspirations for the problem of making a safe chair for kids, compared to "make an object (abstracted problem context) that is safe (concrete constraint)" (which yields inspirations for safety that cannot be applied to chairs).…”
Section: Abstraction During Analogy-findingmentioning
confidence: 99%
“…Most existing experimental studies have N 12 per treatment cell (Chiu and Shu 2012;Hender et al 2002;Malaga 2000); only four studies had N ! 18 (Chan et al 2011;Fu et al 2013;Gonçalves et al 2013;Tseng et al 2008), and they are evenly split in support/opposition for the benefits of far sources. Among the few correlational studies, only Dahl and Moreau (2002) had a well powered study design in this regard, with 119 participants and a reasonable range of conceptual distance.…”
Section: Impetus For the Current Workmentioning
confidence: 99%
“…However, empirical support for this proposal is mixed. Some studies have shown an advantage of far over near sources for novelty, quality, and flexibility of ideation (Chan et al 2011;Chiu and Shu 2012;Dahl and Moreau 2002;Gonçalves et al 2013;Hender et al 2002); but, some in vivo studies of creative cognition have not found strong connections between far sources and creative mental leaps (Chan and Schunn 2014;Dunbar 1997), and other experiments have demonstrated equivalent benefits of far and near sources (Enkel and Gassman 2010;Malaga 2000). Relatedly, Tseng et al (2008) showed that far sources were more impactful after ideation had already begun (vs. before ideation), providing more functionally distinct ideas than near or control, but both far and near sources led to similar levels of novelty.…”
mentioning
confidence: 99%